The effect of giant lateral collapses on magma pathways and the location of volcanism - Francesco Maccaferri (Nature Portfolio, 2017)
Flank instability and lateral collapse are a potential hazard at volcanic edifices. Here, the authors use numerical simulations to show that at Fogo volcano, lateral collapse can trigger a significant deflection of magma pathways in the crust, demonstrating how volcanic edifices may evolve.